Practicum of initial teacher training in three European universities (Cantabria, Padua, and Coimbra): A comparative study - Ángela Saiz Linares; Noelia Ceballos López (Arizona State University, 2019)
The aim of this research is to analyze comparatively the practicum of three European universities, Cantabria, Padua, and Coimbra, which have participated in the process of convergence towards the European Higher Education Area (EHEA). The ultimate purpose of this analysis is to confront its essential aspects in order to learn and advance some elements of improvement for the different systems. Official documents of the practicum programs have been analyzed and 14 semi-structured interviews have been conducted with practicum supervisors from the three countries. The comparative analysis procedure, of a qualitative nature, revolves around five categories of analysis: sense of the practicum in the training process, structure of the practicum, professionals involved and their functions, activities developed and evaluation. The results obtained show concurrences in the definitions of the practicum at the normative level of the three contexts that contrast, in turn, with some divergences with the discourses of the participants, especially in the case of Cantabria and Padua. These differences make sense in some specific actions proposed by these practicum programs that orient this training space towards a more professionalizing pole and sustain a certain split in the theoretical and practical training. The case of Coimbra is, however, more consistent with the definition of the practicum as a moment that allows connecting all the components of training and linking university learning with practice in schools. Some conclusions of improvement derived from the analysis go in line with institutionalizing more reflective moments and activities throughout the practical training and involving students, university teachers and school teachers in more collaborative ways.